Analisis Penggunaan Media Kartu untuk Meningkatkan Kosakata Bahasa Inggris pada Tema Makna Sarana Puja di Sekolah Minggu Buddha Vihara Dhamma Sundara - Dwi Maryani Rispatiningsih (STABN Sriwijaya, 2019)
Objectives of this study are (1) to know the teaching learning process of English subject at Vihara Dhamma Sundara Surakarta by using cards media; (2) to identify obstacles by teaching in Buddha Dhamma Virya Sunday school; and (3) to describe how to deal with obstacles. This research is using qualitative research, while the research method used descriptive research. These subjects of this study are 22 students at Vihara Dhamma Sundara Surakarta. The instrument used in this study is a test. The data collection techniques are using observation, interview, and documentation. For the data analysis techniques are using data reduction, data presentation, and conclusion. Based on the description of the data and data analysis, it is known that students of Buddha Sunday School in learning process using cards media are very enthusiastic and also can increase their vocabulary mastery. The obstacles that occur in teaching learning process using cards media are: time constraints, class management, and the last is different age in this class. Tujuan penelitian ini adalah: (1) mengetahui proses pembelajaran Bahasa Inggris di SMB Vihara Dhamma Sundara dengan menggunakan media kartu; (2) mengetahui kendala-kendala yang dihadapi Sekolah Minggu Buddha; dan (3) mendiskripsikan cara menghadapi hambatan yang terjadi. Penelitian ini merupakan penelitian kualitatif. Metode penelitian yang digunakan adalah metode penelitian deskriptif. Subjek penelitian ini adalah siswaSekolah Minggu Buddha Dhamma Virya, Vihara Dhamma Sundara Surakarta sebanyak 22 siswa. Instrumen yang digunakan adalah tes. Berdasarkan deskripsi data dan analisis data yang telah dilakukan diketahui bahwa siswa Sekolah Minggu Buddha dalam pembelajaran dengan menggunakan media kartu sangat antusias dan dapat meningkatkan kosakatanya. Hal ini didasarkan pada hasil tes yang